Exploring the Characteristics of Student Transformational Activities in Indonesia in Solving Cognitive Conflict-Based Problems - Rosimanidar; Purwanto; Hidayanto, Erry; Sulandra, I Made (JTP - Jurnal Teknologi Pendidikan, 2023)
This research aimed to describe the characteristics of the transformational activities of Indonesian students in resolving problems based on cognitive conflict. The research employed a phenomenological approach with five students as subjects. The research instruments included tests and interview guidelines, and the analysis was conducted using the constant comparative method. Change-based activities are a good way to solve cognitive conflict issues, including full rule-based unexpected results, full rule-based matching problem parts, incomplete rule-based unexpected results, and incomplete rule-based matching problem parts. Exploring these characteristics serves as a foundation for instructors to enhance the quality of instructional design. Practically, a profound understanding of these characteristics can provide a solid foundation for educators to enhance their instructional design quality. By exploring and comprehending how students address cognitive conflict, instructors can design more effective learning experiences that align with the student's needs.